Qualitative Histological Evaluation of Various Decalcifying Agents on Human Dental Tissue - Bumalee, Dusit; Lapthanasupkul, Puangwan; Songkampol, Khumpee; Srimaneekarn, Natchalee; Kitkumthorn, Nakarin; Arayapisit, Tawepong (European Journal of Dentistry, 2022)
Objective Dental hard tissue is among the hardest tissue of humans because it contains high amounts of inorganic substances. This leads to difficulty in preparing histological sections for histopathological examination. Acid and chelating agents are generally used to decalcify teeth. We aimed to compare the histological quality of teeth decalcified with various calcifying agents including 5% nitric acid, 50% formic acid with 20% sodium citrate (Anna Morse solution), 10% formic acid, commercial solution, and 14.4% neutral EDTA.Materials and Methods Freshly extracted premolar teeth were fixed and submitted for decalcification using different agents. Histological examination was qualitatively evaluated for tissue integrity and staining quality.Results Dentin integrity of teeth decalcified with all decalcifying agents did not show any statistical differences except that with the formic acid, whereas cementum integrity decalcified with neutral EDTA showed a superior score compared with other agents. Tissue integrity and staining quality of dental pulp cells were the best decalcified with neutral EDTA or Anna Morse solution.Conclusion Our findings demonstrated that EDTA and Anna Morse solution gave a similar efficiency in the preservation of tissue integrity while Anna Morse solution may be recommended as a decalcification agent in routine use due to the more satisfying decalcification time than EDTA.
Keywords: decalcifying agent; dental; histology; teeth